2019
DOI: 10.1007/s13205-018-1549-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production from agarophyte red seaweed, Gelidium elegans, using a novel sample preparation method for analysing bioethanol content by gas chromatography

Abstract: In this study, Gelidium elegans is investigated for ethanol production. A combination of factors including different temperatures, acid concentration and incubation time was evaluated to determine the suitable saccharification conditions. The combination of 2.5% (w/v) H 2 SO 4 at 120 °C for 40 min was selected for hydrolysis of the seaweed biomass, followed by purification, and fermentation to yield ethanol. The galactose and glucose were dominant reducing sugars in the G. elegans hydrolysate and under optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A significant amount of research has been conducted on bioethanol production from red seaweeds, of which sulphuric acid has been identified to be the most suitable reaction catalyst for the initial pre-treatment stage. This includes studies performed on Kappaphycus alvarezii [15,34] Gelidium amansii [35][36][37], Gracilaria verrucosa [38], Gracilaria tenuistipitata [36], Gelidium elegans [39] and Gracilariopsis chorda [36], where sequential two stage pretreatments (acid pre-treatment followed by enzyme hydrolysis) have been applied, subsequently followed by fermentation to bioethanol. A study by Nguyen et al [35] who identified optimal conditions (180 mM sulphuric acid at 121°C for 45 min at a solids loading content of 12% w/v) for liberating glucose (6.8 g L −1 ) and galactose (26.1 g L −1 ) from G. amansii included an additional detoxification step in order to remove HMF which had reached levels as high as 8.7 g L −1 as a result of the thermal acid pre-treatment.…”
Section: Investigation Of Pre-treatment Conditionsmentioning
confidence: 99%
“…A significant amount of research has been conducted on bioethanol production from red seaweeds, of which sulphuric acid has been identified to be the most suitable reaction catalyst for the initial pre-treatment stage. This includes studies performed on Kappaphycus alvarezii [15,34] Gelidium amansii [35][36][37], Gracilaria verrucosa [38], Gracilaria tenuistipitata [36], Gelidium elegans [39] and Gracilariopsis chorda [36], where sequential two stage pretreatments (acid pre-treatment followed by enzyme hydrolysis) have been applied, subsequently followed by fermentation to bioethanol. A study by Nguyen et al [35] who identified optimal conditions (180 mM sulphuric acid at 121°C for 45 min at a solids loading content of 12% w/v) for liberating glucose (6.8 g L −1 ) and galactose (26.1 g L −1 ) from G. amansii included an additional detoxification step in order to remove HMF which had reached levels as high as 8.7 g L −1 as a result of the thermal acid pre-treatment.…”
Section: Investigation Of Pre-treatment Conditionsmentioning
confidence: 99%
“…In the present study, the ethanol production rate and fermentation e ciency of the acid hydrolysate (AH) were low, due to the presence of galactose as the main reducing sugar in the dilute acid hydrolysate, and the fact that ethanol yield from galactose is lower than glucose (Hong et al 2011;Hessami et al 2019). D-Galactose undergoes conversion via the Leloir pathway; basically, in this pathway, a ve-step enzymatic pathway converts D-Galactose to glucose-6-phosphate (Timson 2007).…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, the ethanol production rate and fermentation e ciency of the acid hydrolysate (AH) were low, due to the presence of galactose as the main reducing sugar in the dilute acid hydrolysate, and the fact that ethanol yield from galactose is lower than glucose (Hong et al 2011;Hessami et al 2019).…”
Section: Discussionmentioning
confidence: 77%